Dynamics of Gill Responses to a Natural Infection with Neoparamoeba perurans in Farmed Tasmanian Atlantic Salmon - Max Charles Vallarino; Sarah L. Dagen; Eoin Costelloe; Shalom Inioluwa Oyenekan; John Tinsley; Victoria Valdenegro; Elżbieta Król; Patricia Noguera; Samuel A. M. Martin (Animals, 2024)
Gill health has become a significant global challenge for Atlantic salmon (Salmo salar) aquaculture, particularly during the marine phase of farming. The increasing prevalence of gill pathologies has been linked to rising seawater temperatures, underscoring the need to evaluate existing tools for monitoring gill health and to develop novel approaches for early detection. In this study, we investigated the gill responses of commercially farmed Atlantic salmon to natural infection with Neoparamoeba perurans during an outbreak of amoebic gill disease (AGD) in Tasmania. Our focus spanned the low AGD prevalence, high AGD prevalence, and post-freshwater treatment stages of the outbreak. Evaluations of gill tissue included assessments of the gross AGD score, histopathological score, abundance of N. perurans (measured by 18S rRNA gene expression), and expression levels of inflammation-related transcripts. We demonstrated a strong correlation between different measures of AGD-related gill pathology and significant differences between distinct stages of the N. perurans outbreak. Post-treatment, fish exhibited considerable variability in their responses to the freshwater bath, highlighting the necessity for personalized management strategies that consider genetic, environmental, and health status factors. The expression patterns of angiogenin-1 (ANG1) and complement C1q tumour necrosis factor-related protein 3-like (C1QTNF3) emphasize their potential as biomarkers for early detection of gill damage in salmon aquaculture worldwide.